1991
DOI: 10.1159/000216196
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Clotting System in the Presence of Heparin and Depolymerized Heparin

Abstract: The kinetics of the activation of the plasmatic clotting system in the presence of heparin and depolymerized heparin (Kabi 2165), respectively, was compared with the kinetics of activation in plasma with isolated factor deficiency. Measurements were made with a chromogenic substrate method using Tos-Gly-Pro-Arg-p-nitroanilide acetate. The extinction curves were analyzed to determine the characteristics of a curve that was fitted to the experimental data to sufficiently describe the slope of the curves by const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…It was observed that the plot of k value versus lag time overlapped for samples with and without heparin ͑not shown͒, indicating that the clotting process follows the same kinetics whether it is accelerated by thromboplastin or delayed by heparin. This is in contradiction to the results presented by others, 9 stating that k is a parameter more sensitive to the clotting kinetics than the lag time. The role of the detection method and the fitting equation needs to be investigated further.…”
Section: Discussioncontrasting
confidence: 99%
“…It was observed that the plot of k value versus lag time overlapped for samples with and without heparin ͑not shown͒, indicating that the clotting process follows the same kinetics whether it is accelerated by thromboplastin or delayed by heparin. This is in contradiction to the results presented by others, 9 stating that k is a parameter more sensitive to the clotting kinetics than the lag time. The role of the detection method and the fitting equation needs to be investigated further.…”
Section: Discussioncontrasting
confidence: 99%
“…Some variations of the PT assay also use the amplitude of signal change during coagulation to estimate fibrinogen concentration (z).Recent studies have attempted to identify ways in which additional information might be extracted from PT and AP[T, using parameters including the rate of coagulation (3,4). For example, we have described a method in which optical data for APTT and PT assays were charactenzedby a set…”
mentioning
confidence: 99%